Analysis of Arabic Learning in the City of Kediri - Asrofil Lailiyah Maruf Ramadhan; Farikh Marzuki Ammar (Indonesian Journal of Islamic Studies, 2022)
Learning Arabic at the Al Farisi Arabic Course Institute in Pare Kediri uses the qowa`id guide book written by Ustadz Salman Faroh as the founder of Al Farisi, and the book Al Muhadatsah wal Muhawaroh billughotil `Arobiyyah as a guide book for muhadatsah classes. Which in the implementation of Arabic language learning at the Al Farisi course institution is taught in stages according to the abilities of students and each level is taught using different materials and methods. The existence of a good learning system is an advantage that the Al Farisi Institute has. Meanwhile, what is part of the shortcomings at Al Farisi are the absence of E-learning for distance learning and the ineffective learning in online learning using Google Meet due to network constraints that do not support it.